2011
DOI: 10.1590/s0103-84782011005000097
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e desenvolvimento corporal de bovinos leiteiros mestiços submetidos a níveis de suplementação em pastagem de Brachiaria brizantha

Abstract: IDesempenho e desenvolvimento corporal de bovinos leiteiros mestiços submetidos a níveis de suplementação em pastagem de Brachiaria brizanthaPerformance and body development crossbred dairy cattle submitted to levels of supplementation in Brachiaria brizantha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…Although there was higher individual heterozygosis of G1 animals, the heterosis was not significant at 8 and 12 month of age, and even though the G2 animals had lower individual heterozygosis, they displayed significant heterosis at all ages because they benefited from the maternal heterosis of their F1 dams. Cerdótes et al (2004) reported that F1 cows produced more milk than purebreds, resulting in higher weight gain of their calves, and according to Rezende et al (2011), the greater rump height of the animals could be explained by higher energy intake. The height of an animal is of fundamental importance because of its positive association with metabolic body size and consequently with its physical requirements (BIF, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there was higher individual heterozygosis of G1 animals, the heterosis was not significant at 8 and 12 month of age, and even though the G2 animals had lower individual heterozygosis, they displayed significant heterosis at all ages because they benefited from the maternal heterosis of their F1 dams. Cerdótes et al (2004) reported that F1 cows produced more milk than purebreds, resulting in higher weight gain of their calves, and according to Rezende et al (2011), the greater rump height of the animals could be explained by higher energy intake. The height of an animal is of fundamental importance because of its positive association with metabolic body size and consequently with its physical requirements (BIF, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The body growth of animals is typically assessed by measuring body weight without association with conformation measurements, however, given the interaction between these two variables, collectively they would better represent the growth of individuals (REZENDE et al, 2011). Evaluating an animal by its body weight alone might be considered rather imprecise (PEREIRA et al, 2010), because several environmental factors such as nutrition, management, and physiological and/or pathological factors may affect animal performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O maior aporte energético e proteico resultante do maior nível de suplementação provavelmen- Constatou-se diferença significativa (P>0,05) para medida final do comprimento da garupa em favor dos animais submetidos à taxa de lotação de 2 UA/ha e suplementação de 12,0 g/kg de PC indicando, provavelmente, que esses animais aumentaram o crescimento ósseo em função do maior aporte de nutrientes. REZENDE et al (2011) avaliando as medidas corporais de bovinos mestiços castrados Holandês/ Zebu, com seis meses de idade e PC inicial de 118±16 kg, mantidos em pastagem de Brachiaria brizantha, o período de transição água/seca. Verificaram que os animais que receberam suplemento energético em quantidade equivalente a 1,0% do PC apresentaram maiores patamares para medidas corporais finais de perímetro torácico, altura na cernelha e da garupa em relação aqueles suplementados com nível de 0,5% do PC.…”
Section: Resultsunclassified
“…Na mesma ocasião realizaram-se as mensurações corporais que foram analisadas em função dos parâmetros: inicial, final e de ganho no período total do confinamento. Foram obtidas: altura da cernelha, correspondendo à distância da cernelha até a superfície do solo; altura da garupa, correspondendo à distância do osso sacro até a superfície do solo, sendo estas medidas tomadas com auxílio de bastão graduado e fita métrica; perímetro torácico, que corresponde ao perímetro imediatamente caudal à escápula passando pelo externo e pelos processos espinhais das vértebras torácicas; perímetro de canela, mensurado a partir do diâmetro do osso metacarpiano no membro anterior direito e comprimento, mensurado em linha reta entre a articulação escápulo-umeral e a tuberosidade coxal do ílio tomada lateralmente com auxílio de fita métrica, conforme descrita por Rezende et al (2011). Na análise de variância, para as variáveis estudadas, cada animal constituiu uma unidade experimental.…”
Section: Methodsunclassified